Sites D’eau Sacrés Et Conservation De La Biodiversité : Cas Des Paysages D’eau De La Région De Ziguinchor (Sénégal) - Mamadou Lamine Sané; Claudette Soumbane Diatta; Barnabé Ephrem A. Diémé (European Scientific Journal, ESJ, 2021)
The region of Ziguinchor, located in the south of Senegal, is entirely within Lower Casamance. Populated mainly by Ajamaat, this region is characterized geographically by a predominance of water landscapes that give it the image of an "amphibious" territory. This aquatic environment dominated by the Casamance River from which many bolongs stand out is also made up of mangroves, shallows and multitudes of ponds associated with them. The ajamaat populations thus draw an essential part of their resources from this environment. However, beyond its nourishing aspect, the aquatic environment occupies an important place in the traditional ajamaat beliefs. Considered as sanctuaries for many beings who populate the religious universe ajamaat, the water landscapes of Lower Casamance are sacred spaces whose access is subject to prohibitions. This aspect reflects the contribution of beliefs in the preservation of biodiversity.La région de Ziguinchor, située au sud du Sénégal, est entièrement comprise dans la Basse Casamance. Peuplée essentiellement par des Ajamaat, cette région se caractérise au plan géographique par une prédominance des paysages de l’eau qui lui donnent l’image d’un territoire « amphibie ». Cet environnement aquatique dominé par le fleuve Casamance d’où se détachent de nombreux bolong est aussi constitué de mangroves, de bas-fonds et de multitudes de mares qui leurs sont associées. Les populations ajamaat tirent ainsi une part essentielle de leurs ressources dans ce milieu. Toutefois, au-delà de son aspect nourricier, l’environnement aquatique occupe une place importante dans les croyances traditionnelles ajamaat. Considérés comme sanctuaires de nombreux êtres qui peuplent l’univers religieux ajamaat, les paysages de l’eau de la Basse Casamance sont des espaces sacrés dont l’accès est soumis à des interdits. Cet aspect traduit l’apport des croyances dans la préservation de la biodiversité.